Study on the intervention effect of HCH integrated SMG health management model on community high-risk group of cardiovascular disease - Du, Rui; Ma, Kaifang; Li, Yanru; Tian, Jin; Li, Mengkun; Zhao, Chenxi; Wang, Jing (Frontiers in Cardiovascular Medicine, 2024)
Objective This study aimed to evaluate the integration of the Hospital-Community-Home (HCH) model with the Self-Mutual-Group (SMG) health management model for high-risk populations with cardiovascular disease in the Yuhua community of Shijiazhuang city. The study focused on implementing care interventions (HCH, SMG) with a specific emphasis on SMG to promote beneficial views/behaviors, enhance self-efficacy/agency, and address detrimental determinants of health, ultimately leading to durable changes and healthier lifestyles. Comparing the HCH model with the combined SMG model helps to comprehensively assess the strengths and weaknesses of different health management approaches. This comparison contributes to theoretical innovation and practical development in the field of health management, as well as improving patients' health outcomes and quality of life. Methods This study employed a quasi-experimental design. Using stratified sampling, individuals who underwent health examinations in Community A and Community B from Shijiazhuang city between May 2023 and August 2023 were randomly selected. After informing the participants about the study and obtaining informed consent via telephone, high-risk patients with cardiovascular disease were screened based on their medical examination reports. Data on lifestyle behaviors, self-efficacy, medical responses, quality of life, and readmission rates were collected and compared before and after the intervention. Results A total of 526 eligible participants were included, with 241 in the control group and 285 in the study group. After the intervention, there was no significant change in the proportions of smokers, alcohol consumers, and individuals engaging in leisure exercises in the control group. However, in the study group, the proportions of smokers and alcohol consumers significantly decreased, while the proportion of individuals engaging in leisure exercises significantly increased. After the intervention, both the study group and the control group showed significant increases in scores on the General Self-Efficacy Scale—Schwarzer (GSES) and the Seattle Angina Questionnaire (SAQ), with the study group scoring significantly higher than the control group. Avoidance and surrender scores significantly increased after the intervention, with the study group scoring significantly lower than the control group. Confrontation scores significantly increased after the intervention, with the study group scoring significantly higher than the control group. During the follow-up period, the study group had a significantly lower readmission rate than the control group. Conclusion The integration of HCH with SMG health management model can significantly improve lifestyle behaviors, optimize medical responses, enhance self-efficacy and quality of life, and significantly reduce readmission rates among high-risk populations with cardiovascular disease.